Percutaneous transluminal angioplasty of the external carotid artery. - Vitek, J J (American Journal of Neuroradiology, 1983)
Percutaneous transluminal angioplasty was used to treat stenotic lesions in 10 external carotid arteries in nine patients. Four representative cases are described. Nine arteries were successfully dilated. One attempt failed because the catheter could not be passed through the stenosis. Spasm of the distal external carotid artery due to guide wire-catheter manipulation was seen in six patients. No serious complications were encountered.